Targeting RARγ Decreases Immunosuppressive Macrophage Polarization and Reduces Tumor Growth - Jihyeon Park; Jisun Oh; Sang-Hyun Min; Ji Hoon Yu; Jong-Sup Bae; Hui-Jeon Jeon (Molecules)
Tumor-associated macrophages (TAMs) play a critical role in the tumor microenvironment (TME), interacting with cancer cells and other components to promote tumor growth. Given the influence of TAMs on tumor progression and resistance to therapy, regulating the activity of these macrophages is crucial for improving cancer treatment outcomes. TAMs often exhibit immunosuppressive phenotypes (commonly referred to as M2-like macrophages), which suppress immune responses and contribute to drug resistance. Therefore, inhibiting immunosuppressive polarization offers a promising strategy to impede tumor growth. This study revealed retinoic acid receptor gamma (RARγ), a nuclear receptor, as a key regulator of immunosuppressive polarization in THP-1 macrophages. Indeed, the inhibition of RARγ, either by a small molecule or gene silencing, significantly reduced the expression of immunosuppressive macrophage markers. In a three-dimensional tumor spheroid model, immunosuppressive macrophages enhanced the proliferation of HCT116 colorectal cancer cells, which was significantly hindered by RARγ inhibition. These findings suggest that targeting RARγ reprograms immunosuppressive macrophages and mitigates the tumor-promoting effects of TAMs, highlighting RARγ as a promising therapeutic target for developing novel anti-cancer strategies.